Decisões de preço e propaganda em um oligopólio considerando o processo de difusão da inovação - Daniel Teixeira Eloi Santos (2009)
Literature on innovation diffusion has been developed for decades and its importance has been growing lately due to the attention being paid to innovation by recent papers. However, current research seems more proper for dealing with monopolistic markets or monopolistic competition, as competitor actions have little influence on a companys market payoff. Motivated by the practical relevance and the gap in the current literature on innovation diffusion and future cash flows estimation, we developed a game theoretical model based on General Bass Model (GBM) for predicting innovations potential reward throughout its life-cycle in oligopolistic markets. The present paper considers the problem of pricing and advertizing competition in an oligopolistic market of an innovative product. We focus on the situation in which two companies launch simultaneously similar, but not identical, products into the market and compete throughout their lifecycle. Results obtained on this research are useful for guiding managers in innovative and competitive situations and also in favor of estimating marketing payoffs for innovative products. We analyze three main scenarios: price equilibria, advertizing equilibria, and price and advertizing equilibria simultaneously. Besides guiding managers making pricing and advertizing decisions, the proposed model helps managers planning the substitution of a certain product generation and planning capacity and production throughout product lifecycle.